On the Use of Semi-empirical Flame Models for Spreading Chaparral Crown Fire - Cobian-Iñiguez, Jeanette; Aminfar, AmirHessam; Weise, David R.; Princevac, Marko (Frontiers in Mechanical Engineering, 2019)
Flame geometry plays a key role in shaping fire behavior as it can influence flame spread, radiative heat transfer and fire intensity. For wildland fire, thorough characterizations of flame geometry can help advance the derivation of comprehensive models of wildfire behavior. Within the fire community, a classical flame modeling approach has been to develop semi-empirical models. Many of these models have been derived for surface fuels or for pool fire configurations. However, few have sought to model flame behavior in chaparral crown fires. Thus, the objective of this study is to assess the applicability of semi-empirical models on observed chaparral crown fire behavior. Semi-empirical models of flame tilt, flame height, and flame length from the literature are considered. Comparison with experimental observation of flame height in the crown fuel layer, showed good agreement between the 2/5th power law that relates flame height to heat release rate. Two new power-law correlations relating flame tilt angle to Froude number are proposed. The coefficients for new models are obtained from regression analysis.